Criminal Trajectory of Women Detained by the Chilean Police (Carabineros) for Crimes of Domestic Violence in 2007 and Followed up to 2016 [Trayectoria Criminal de Mujeres Detenidas por Carabineros de Chile en 2007 por Violencia Intrafamiliar, Seguidas Hasta 2016 - Garrido-Gonzalez, J (Universidad de Caldas, 2023)
The objective of this work is to identify the evolution of criminal behavior throughout the life of a group of 824 women detained by the Chilean police for crimes of domestic violence in 2007. The design is pseudo prospective longitudinal, which allows its follow-up through 9 years, as if it corresponded to a prospective longitudinal study. Any new detention or complaint against them between the years 2007 and 2016 was considered a recidivism. The 60.6% of women reoffended accumulating a total of 2,583 crimes. The criminal trajectories of this population extended well beyond the age of 30, generating an elongated age/crime curve, given that an important part of these women continued committing crimes until they were 40 years old, moving away from the traditional way that the age/crime curve acquires. © (2023). All Rights Reserved.
Keywords: age/crime curve; criminal trajectories; female delinquency; intrafamily violence; recidivism